Polyvinylidene fluoride supercritical foaming production process

By introducing nano-scale porous materials and multi-layer expansion technology into the polyvinylidene fluoride supercritical foaming process, the problem of uneven bubble structure in traditional foaming processes is solved, and the high performance and multi-layer functionality of foam materials are achieved , suitable for high-demand application areas.

CN119161623APending Publication Date: 2024-12-20苏州凯之柏材料科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411365677.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The bubble structure in the existing foaming process is uneven, resulting in poor performance of foam materials in mechanical properties and thermal insulation properties, and the inability to take into account the multi-layer functional requirements of the materials, which limits its promotion in high-demand applications.

Method used

Polyvinylidene fluoride supercritical foaming production process is adopted, by mixing polyvinylidene fluoride with nano-scale porous materials, extruding into a plate using a twin-screw extruder, and preheating, nitrogen diffusion and The rapid pressure reduction step is used to form uniform bubble crystal nuclei, and then a multi-layer foam structure of a high-density core layer, a medium-density intermediate layer and a low-density outer layer is formed by multi-layer expansion treatment.

Benefits of technology

It realizes the high uniformity of the bubble structure, improves the mechanical properties, thermal insulation properties and lightweight design of the material, ensures the stability and durability of the material under complex working conditions such as high pressure and high temperature. It is suitable for automobiles, aerospace, etc. High demand areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161623A_ABST
    Figure CN119161623A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of foaming production, and discloses a polyvinylidene fluoride supercritical foaming production process which comprises the following steps: (a) mixing polyvinylidene fluoride with a nanoscale porous material with the particle size of 50-150nm; (b) extruding the mixed polyvinylidene fluoride material into a plate by using a double-screw extruder, and carrying out crosslinking treatment after extrusion; (c) carrying out preheating treatment on the extruded plate at the temperature of 220 DEG C for 10-15 minutes so as to further enhance the cross-linking reaction; a nanoscale porous material is introduced into a polyvinylidene fluoride matrix, so that the diffusion rate of nitrogen in the material is remarkably improved. The introduction of the nanoscale porous material forms a uniform microchannel network, so that nitrogen can more uniformly permeate into the material in a high-pressure environment, the uniform nitrogen diffusion ensures that the formation of bubbles is more consistent, and the problems of different sizes and unstable structure of the bubbles in the traditional process are effectively avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foaming production, in particular to a supercritical foaming production process of polyvinylidene fluoride. Background Art

[0002] With the widespread application of high-performance polymer materials in the fields of automobiles, aerospace, building insulation, etc., the market demand for foam materials with excellent mechanical properties, thermal insulation, lightweight and chemical corrosion resistance is increasing. Among them, polyvinylidene fluoride (PVDF) has gradually become the preferred material in many fields due to its good chemical stability, high temperature tolerance and mechanical properties. In order to further improve its performance, the existing technology has begun to focus on the foaming process, which forms a fine bubble structure in the PVDF matrix to give it excellent thermal insulation, shock absorption and mechanical properties.

[0003] The existing foaming process mainly uses physical foaming agents or chemical foaming agents to generate bubbles inside the material under normal temperature and pressure conditions. This type of process is usually simple and easy to operate, with low production costs, but its main disadvantages are that the bubble structure is not uniform enough and the diffusion efficiency of the foaming agent is limited, resulting in fluctuations in the density and mechanical properties of the foamed material. In addition, the traditional foaming process has bottlenecks in the lightweight design of foam materials and cannot take into account the multi-level functional requirements of the material, limiting its further promotion in high-demand application fields.

[0004] In the prior art, the traditional foaming process generally has the problem of uneven bubble structure. Due to the limited diffusion of the foaming agent, bubbles of different sizes are easily formed inside the material, resulting in poor mechanical and thermal insulation properties of the foam material. Especially when dealing with complex working conditions such as high pressure and high temperature, this uneven bubble structure may cause local stress concentration in the material, affecting the overall strength and durability of the material. Therefore, how to achieve a high degree of uniformity in the bubble structure has become a key problem that needs to be solved in the prior art. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a supercritical foaming production process for polyvinylidene fluoride, which solves the problem of uneven bubble structure commonly existing in traditional foaming processes.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: a polyvinylidene fluoride supercritical foaming production process comprises the following steps:

[0007] (a) mixing polyvinylidene fluoride with a nano-porous material, wherein the particle size of the nano-porous material is 50-150 nm;

[0008] (b) using a twin-screw extruder to extrude the mixed polyvinylidene fluoride material into a sheet, and performing a cross-linking treatment after extrusion;

[0009] (c) preheating the extruded sheet at 220° C. for 10-15 minutes to further enhance the crosslinking reaction;

[0010] (d) placing the plate into an autoclave, heating it to 250° C., increasing the pressure to 675 bar, and maintaining it for 8 hours, so that nitrogen diffuses into the plate through the nanoporous material;

[0011] (e) forming uniform bubble nuclei through a rapid depressurization step;

[0012] (f) The sheet is subjected to a multi-layer expansion treatment in a low-pressure autoclave, and the pressure is gradually reduced to form a multi-layer foam structure.

[0013] Preferably, the nano-scale porous material is silicon dioxide or aluminum oxide, and the added amount of the nano-scale porous material is 0.5%-5% of the total weight of polyvinylidene fluoride.

[0014] Preferably, the screw speed of the twin-screw extruder is set to 50-150 rpm, the extrusion temperature is 180° C. to 230° C., and the extrusion pressure is controlled between 5-10 MPa.

[0015] Preferably, the thickness of the plate after the preheating step is 5-10 mm.

[0016] Preferably, the pressure reduction rate of the rapid pressure reduction step is 1-5 bar / sec.

[0017] Preferably, the multi-layer expansion step comprises the following steps:

[0018] The first expansion is carried out at a pressure of 17 bar to form a high-density core layer, and the expansion multiple is 3 times the original volume;

[0019] The pressure is reduced to 10 bar and a second expansion is performed to form a medium-density middle layer with an expansion multiple of 5-6 times;

[0020] The pressure is further reduced to 1-2 bar to form a low-density outer layer with an expansion multiple of 8-10 times.

[0021] Preferably, the cell density of the high-density core layer is 10^6 to 10^7 per cubic centimeter.

[0022] Preferably, the cell density of the medium-density middle layer is 10^5 to 10^6 per cubic centimeter.

[0023] Preferably, the cell density of the low-density outer layer is 10^4 to 10^5 per cubic centimeter.

[0024] Preferably, the foam material is cooled to 60° C. after expansion is completed, with a cooling rate of 5° C. / min.

[0025] The present invention provides a supercritical foaming production process for polyvinylidene fluoride, which has the following beneficial effects:

[0026] 1. The present invention significantly improves the diffusion rate of nitrogen in the material by introducing nano-porous materials into the polyvinylidene fluoride matrix. The introduction of nano-porous materials forms a uniform micro-channel network, allowing nitrogen to penetrate more evenly into the material under high pressure. This uniform nitrogen diffusion ensures more consistent bubble formation, effectively avoiding the problems of uneven bubble size and unstable structure in traditional processes.

[0027] 2. The present invention forms uniform bubble nuclei by rapid pressure reduction and adopts multi-layer structure expansion technology to optimize the internal cell structure of the material, ensuring that the cell density and expansion multiple of each layer match. The high-density core layer provides the material's compressive strength, the medium-density layer provides elasticity and thermal insulation, and the low-density outer layer has good shock absorption and energy absorption effects.

[0028] 3. The multi-layer expansion structure adopted by the present invention can effectively reduce heat conduction by controlling the density of the pores at different levels. The high-density pores in the core layer provide a stable material structure, while the low-density pore structure in the middle and outer layers effectively blocks heat transfer, further enhancing the thermal insulation effect of the material.

[0029] 4. The present invention uses a multi-layer structure expansion process, which can achieve lightweighting of the material without sacrificing the mechanical properties of the material. The low-density outer layer structure reduces the overall quality of the material, but its heat insulation, shock absorption and other functions are retained or enhanced.

[0030] 5. The nitrogen saturation time and pressure reduction process in this process are precisely controlled, so that the nitrogen can diffuse quickly and evenly into the material. Compared with the traditional physical foaming process, the present invention achieves a faster foaming rate and higher material consistency through supercritical nitrogen diffusion technology.

[0031] 6. The PVDF foam material prepared by the present invention has excellent mechanical properties, thermal insulation properties, chemical tolerance, and resistance to ultraviolet rays and nuclear radiation, and is suitable for multiple fields such as automobiles, aerospace, building insulation, industrial insulation, etc. The material itself also has good chemical corrosion resistance and high temperature stability, further expanding its application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Embodiment 1:

[0035] Please refer to the attached Figure 1 The embodiment of the present invention provides a supercritical foaming production process for polyvinylidene fluoride, comprising the following steps:

[0036] 1. Raw material preparation and extrusion

[0037] Step 1: Mix the ingredients

[0038] In this embodiment, polyvinylidene fluoride (PVDF) is used as the main substrate, and a PVDF powder material with a melt index of 10-20 g / 10 min is selected. In order to improve the pore uniformity and nitrogen diffusion efficiency of the material, a nano-scale porous material (such as silicon dioxide or aluminum oxide) is added, and its particle size is controlled between 50-150 nm, and the specific addition ratio is 0.5%-5% of the total weight of the PVDF substrate.

[0039] In this process, PVDF powder and nano-scale porous materials are mixed by high-speed stirring equipment at a stirring speed of 500-1000rpm for 15-30 minutes to ensure that the nanoparticles are evenly distributed in the PVDF matrix. After the mixing is completed, the nanoparticles are evenly distributed to form a microporous network structure.

[0040] Step 2: Twin-screw extrusion

[0041] In this embodiment, the mixed PVDF matrix is ​​extruded through a twin-screw extruder. The temperature of each section of the extruder is controlled at 180°C to 230°C to ensure good melting and fluidity of the material, and the screw speed is set at 50-150rpm to ensure the mixing and plasticizing effect of the material.

[0042] During the extrusion process, in order to further enhance the structural strength of the material and ensure that the foam material has sufficient mechanical properties in the subsequent steps, an organic peroxide crosslinking agent (such as dicumyl peroxide) is added, and its concentration is controlled at 1%-3%. This crosslinking agent is activated by high temperature during the extrusion process, and a partial crosslinking reaction occurs, and the degree of crosslinking is controlled at 20%-30%.

[0043] The extruder extrude the material into 5-10mm thick sheets, which are immediately cooled to room temperature after extrusion to avoid excessive thermal degradation or material deformation.

[0044] 2. Nano-scale nitrogen saturation

[0045] Step 3: Heating and Pressurizing the Autoclave

[0046] In this embodiment, the preliminarily extruded and partially cross-linked sheet is loaded into an autoclave. In order to ensure sufficient diffusion of nitrogen in the sheet, the temperature of the autoclave is gradually increased to 250°C, and the heating rate is controlled at 10°C / min to avoid structural instability caused by material temperature fluctuations.

[0047] When the temperature stabilizes, high-purity nitrogen is filled into the autoclave at a rate of 50 bar / min until the pressure inside the autoclave reaches 675 bar. Under high pressure conditions, nitrogen can diffuse into the PVDF matrix through the microchannels formed by the nano-porous material, ensuring that the internal structure of the board is saturated with nitrogen.

[0048] The key in this step is to maintain high pressure for 8 hours to ensure that the nitrogen can fully penetrate every corner of the plate and avoid the problem of uneven distribution of bubbles in the material.

[0049] Step 4: Rapid pressure drop nucleation

[0050] In this embodiment, after nitrogen saturation is completed, the pressure is rapidly reduced through the control system, and the pressure reduction rate is controlled at 1-5 bar / sec, so that uniform bubble nuclei are formed in the plate. Control of the pressure reduction rate is very critical. Too fast pressure reduction will cause the bubbles in the plate to generate too much expansion force, thereby destroying the structure of the material; while too slow pressure reduction may lead to insufficient bubble formation, affecting the uniformity of the final foam material.

[0051] During the rapid depressurization process, nitrogen changes from high pressure to lower pressure, driving the formation of stable nanoscale bubble nuclei inside the material, and the bubbles are evenly distributed, laying the foundation for the subsequent expansion step.

[0052] 3. Multilayer structure expansion process

[0053] Step 5: Initial Expansion

[0054] In this embodiment, the plate formed by rapid decompression to form a crystal nucleus is transferred to a low-pressure autoclave for initial expansion. The initial pressure of the low-pressure autoclave is set to 17 bar, and the temperature in the autoclave is maintained at 250°C. At this time, the internal structure of the material begins to change due to the expansion of nitrogen, and the core layer of the material begins to expand, and the expansion multiple is controlled to be 3 times of the original volume.

[0055] This process is the formation stage of the high-density core layer. The expansion multiple of the core layer and the bubble size have a decisive influence on the mechanical properties of the final foam material. Therefore, it is necessary to control the depressurization rate and expansion time to ensure that the internal structure of the material is uniform.

[0056] Step 6: Multi-layer expansion

[0057] After the core layer is expanded, in this embodiment, the pressure of the low-pressure autoclave is further reduced to 10 bar, and the material continues to expand. At this time, the middle layer of the material begins to expand, and the expansion multiple increases to 5-6 times, forming a medium-density middle layer. The expansion of the middle layer can provide better thermal insulation and buffering effects, especially in thermal insulation applications.

[0058] Subsequently, the pressure in the autoclave is further reduced to 1-2 bar, and the outer layer of the material begins to expand by 8-10 times, forming a low-density outer layer structure. The bubbles in the outer layer structure are large, with good energy absorption and shock absorption effects, and are suitable for application scenarios that require impact resistance and shock absorption.

[0059] Step 7: Cooling and shaping

[0060] In this embodiment, after the expansion is completed, the material needs to be cooled. The material in the low-pressure autoclave is gradually cooled to 60°C, and the cooling rate is controlled at 5°C / min to avoid shrinkage or stress concentration of the internal structure due to rapid cooling of the material. During the cooling process, the bubble structure of the material is finalized, the internal structure is stabilized, and the size of the material is gradually fixed.

[0061] The cooled material is taken out of the autoclave and prepared into foam boards of required size through further cutting process. The material has a high-density core layer, a medium-density middle layer and a low-density outer layer, which can meet the requirements of material density and function in different application fields.

[0062] Embodiment 2:

[0063] This embodiment is based on the first embodiment, and only changes the parameter settings of the nitrogen saturation stage.

[0064] Changing variable: Nitrogen saturation time

[0065] In this embodiment, all process steps are consistent with those in embodiment 1, and the only difference is the setting of nitrogen saturation time. In this embodiment, the nitrogen saturation time is reduced to 4 hours, and the other parameters (such as temperature, pressure, depressurization rate, etc.) remain unchanged.

[0066] The specific steps include:

[0067] Raw material preparation and extrusion

[0068] The same polyvinylidene fluoride (PVDF) substrate and nano-porous material were selected as in Example 1, the particle size of the nanoparticles was still 50-150 nm, and the addition ratio was 0.5%-5%. The temperature, screw speed and pressure parameters of the mixing and extrusion process were kept consistent with those in Example 1. The thickness of the plate obtained after extrusion was controlled to be 5-10 mm.

[0069] Nitrogen saturation process

[0070] In this example, the preliminarily cross-linked PVDF sheet was placed in an autoclave, and the temperature was heated to 250°C and the pressure was increased to 675 bar. However, the nitrogen saturation time was reduced to 4 hours to simulate the situation where nitrogen diffusion was incomplete in a shorter time. The remaining conditions in this step were the same as those in Example 1.

[0071] Rapid decompression nucleation

[0072] In this embodiment, after the nitrogen saturation process is completed, the pressure is rapidly reduced according to the pressure reduction rate (1-5 bar / sec) in the first embodiment to form bubble nuclei. Since the nitrogen diffusion time is reduced, the uniformity of the nuclei may be affected.

[0073] Multi-layer structure expansion

[0074] The expansion steps in this embodiment are the same as those in the first embodiment, including initial expansion (pressure of 17 bar, expansion multiple of 3 times), second expansion (pressure of 10 bar, expansion multiple of 5-6 times), and third expansion (pressure of 1-2 bar, expansion multiple of 8-10 times). After expansion, gradual cooling is performed at a cooling rate of 5°C / min.

[0075] Embodiment three:

[0076] This embodiment is based on the first embodiment, and changes the amount of nano-scale porous material added to verify the effect of the proportion of nano-materials on nitrogen diffusion, foam structure uniformity and final material performance.

[0077] Changing variables: the amount of nanoporous material added

[0078] In this embodiment, the amount of nano-porous material (such as silicon dioxide or aluminum oxide) added is increased from 0.5%-5% in the first embodiment to 10%. The remaining process steps and parameters are consistent with the first embodiment.

[0079] Raw material preparation and extrusion

[0080] In this embodiment, the same polyvinylidene fluoride (PVDF) substrate is selected, and the melt index is 10-20g / 10min. The difference is that the amount of the nano-porous material added is increased to 10% of the total weight of the PVDF. The mixing process of the material is still carried out using a high-speed stirrer, with a stirring speed of 500-1000rpm and a stirring time of 15-30 minutes to ensure that the nanoparticles are evenly distributed in the substrate.

[0081] Subsequently, the sheet is extruded through a twin-screw extruder, and the temperature, screw speed, extrusion pressure and sheet thickness are controlled in the same manner as in Example 1.

[0082] Nitrogen saturation process

[0083] Similar to Example 1, the preliminarily cross-linked sheet was placed in an autoclave, the temperature was raised to 250°C, the pressure reached 675 bar, and maintained for 8 hours. As the addition ratio of the nano-porous material increased to 10%, it is expected that under high pressure conditions, the pore structure in the material will be more dense, which will have a certain impact on the diffusion path of nitrogen.

[0084] Rapid decompression nucleation

[0085] After nitrogen saturation is completed, the pressure is rapidly reduced at the pressure reduction rate (1-5 bar / sec) of Example 1 to form bubble nuclei. Due to the increase in the content of nanoparticles, the nitrogen diffusion path is complicated, which may lead to a decrease in nitrogen diffusion efficiency in some areas, affecting the uniformity of the nuclei.

[0086] Multi-layer structure expansion

[0087] The multi-layer expansion steps of this embodiment are consistent with those of the first embodiment, including initial expansion (pressure of 17 bar, expansion multiple of 3 times), second expansion (pressure of 10 bar, expansion multiple of 5-6 times) and third expansion (pressure of 1-2 bar, expansion multiple of 8-10 times). After expansion, the material is also gradually cooled to 60°C at a rate of 5°C / min and shaped.

[0088] Comparative test:

[0089] Comparison of nitrogen saturation time (Example 1 and Example 2):

[0090] Variable: Nitrogen saturation time

[0091] The nitrogen saturation time in Example 1 is 8 hours, which is reduced to 4 hours in Example 2.

[0092] Comparison results:

[0093] Bubble uniformity: The bubble uniformity score of Example 1 is 9 points, which is better than 6 points of Example 2, indicating that a longer saturation time is conducive to the uniform diffusion of nitrogen inside the material.

[0094] Compressive strength: The compressive strength of Example 1 is 1.8 MPa, which is higher than 1.2 MPa of Example 2, indicating that a longer saturation time can form a more stable material structure.

[0095] Thermal insulation performance: The thermal insulation performance of Example 1 (0.03 W / m·K) is better than that of Example 2 (0.05 W / m·K), which shows the influence of saturation time on thermal insulation performance.

[0096] Comparison of Nanoparticle Content (Example 1 and Example 3):

[0097] Variable: Nanoparticle content

[0098] The content of nanoparticles in Example 1 is 5%, and in Example 3 it is increased to 10%.

[0099] Comparison results:

[0100] Bubble uniformity: The bubble uniformity score of Example 1 is 9 points, which is higher than 7 points of Example 3, indicating that an appropriate amount of nanoparticles can maintain the uniformity of the bubble structure of the material, while too many nanoparticles may affect the nitrogen diffusion path.

[0101] Compressive strength: Although the compressive strength of Example 3 (1.5 MPa) is higher than that of Example 2, it is lower than that of Example 1, indicating that excessive nanoparticles may cause local stress concentration.

[0102] Thermal insulation performance: The thermal insulation performance of Example 1 is 0.03 W / m·K, which is better than 0.04 W / m·K of Example 3, further proving that too high a proportion of nanoparticles will have a negative impact on the thermal insulation performance of the foam material.

[0103] Table 1 Comparison table of experimental data of embodiment

[0104]

[0105] The density of the foam material in Example 2 is uneven, especially in the distribution of the pore structure. Due to the reduction of nitrogen saturation time, the bubbles inside the material are sparsely distributed, the bubble sizes vary greatly, and large bubble aggregation occurs in some areas, resulting in a decrease in the mechanical properties of the material.

[0106] Compared with Example 1, the material prepared in Example 2 showed greater volatility in the compressive strength test, especially in the strength of the high-density core layer and the medium-density middle layer. Due to the uneven distribution of bubbles, the material in Example 2 showed a higher deformation rate in the compression test and poor elastic recovery.

[0107] The thermal insulation performance of Example 2 is lower than that of Example 1. Due to the unevenness of the pore structure, the thermal conductivity of the material in the thermal insulation performance test is high, especially in the medium and low density layers, and the thermal insulation performance is not as stable as the multilayer structure of Example 1.

[0108] In Example 2, due to the reduction of nitrogen saturation time, the bubble nuclei are uneven, which eventually leads to uneven distribution of bubbles in the material and reduced mechanical properties. In Example 1, by extending the nitrogen saturation time to 8 hours, the nitrogen is fully diffused, the bubbles in the material are evenly distributed, and the mechanical properties are more stable.

[0109] The material in Example 1 exhibits better thermal insulation performance due to uniform bubbles and stable layered structure, while the thermal insulation performance of Example 2 is reduced due to uneven bubbles.

[0110] Embodiment 1 is proved to be the best embodiment by optimizing nitrogen saturation time, ensuring uniformity of bubble crystal nuclei, and improving mechanical properties and thermal insulation.

[0111] The material density of Example 3 is higher than that of Example 1, especially the core layer and the middle layer show higher density values. Due to the high content of nanoparticles, the diffusion path of nitrogen becomes more complicated, and the bubble structure inside the material becomes more uneven, especially between the high-density core layer and the low-density outer layer, the bubble size difference is significant.

[0112] The foam material of Example 3 shows high compressive resistance in the compressive strength test, but due to the uneven bubbles, the stress concentration in the local area is more obvious, which makes the material prone to cracks or breakage in the high stress area, and the mechanical properties are not as stable as those of Example 1.

[0113] The heat insulation performance of Example 3 is slightly lower than that of Example 1. Due to the increase in the content of nanomaterials, the bubble structure in some areas collapsed or became irregular, which affected the heat insulation performance of the material and increased the thermal conductivity.

[0114] In Example 3, the amount of nanomaterial added was increased to 10%, which made the micropore structure inside the material too complicated, affecting the uniformity of nitrogen diffusion, resulting in uneven distribution of the bubble structure. Compared with Example 1, the mechanical properties and thermal insulation properties of Example 3 were reduced, especially when cracks or uneven bubbles appeared at the stress concentration point.

[0115] The addition ratio of the nano material in Example 1 is controlled between 0.5% and 5%, which ensures the uniformity of the material during the nitrogen diffusion process and avoids the adverse effects of excessive nano material content on the foam structure.

[0116] Therefore, the first embodiment optimizes the addition ratio of nanomaterials, so that the material is superior to the third embodiment in terms of mechanical properties, thermal insulation properties and bubble uniformity.

[0117] Comparative Example 1:

[0118] In order to compare the effect of the foaming process, the following provides a traditional foaming process as a comparative example. The traditional process uses a conventional physical foaming agent for foaming, does not use nano-porous materials and nitrogen supercritical diffusion technology, and specifically includes the following steps:

[0119] Raw material preparation: In the traditional process, pure polyvinylidene fluoride (PVDF) is used as the foaming substrate without adding nano-porous materials or other special additives. The foaming agent uses a conventional physical foaming agent (such as CO2 or chemical foaming agent), and the addition amount is 1%-3% of the total weight of the polymer.

[0120] Mixing and extrusion: PVDF and foaming agent are mixed in a mixer for 10 minutes at a speed of 500 rpm. After mixing, the material is extruded through a twin-screw extruder at a temperature of 170°C to 220°C and an extrusion speed of 100 rpm. The thickness of the extruded sheet is controlled at 5-10 mm.

[0121] Foaming process: The board is foamed in a conventional oven, the foaming temperature is set at 150℃ to 180℃, and the foaming time is 20 minutes. The physical foaming agent generates gas during the heating process to form a foam structure.

[0122] Cooling and shaping: The foamed material is naturally cooled to room temperature and shaped. The cooling process does not use an autoclave or special expansion equipment. The pore structure of the material is mainly formed by the expansion of the foaming agent gas.

[0123]

[0124]

[0125] Bubble uniformity and material density: Since the traditional process does not use nano-porous materials, the gas cannot diffuse evenly during the foaming process, resulting in uneven bubble structure. The bubble uniformity score is 5 points and the material density is 130kg / m 3 , compared with the density of Example 1 (100kg / m 3 ) is higher and the bubbles are unevenly distributed.

[0126] Mechanical properties: The compressive strength of the conventional process is 1.0 MPa, which is significantly lower than the 1.8 MPa of Example 1, indicating that the material has poor bearing capacity under compressive loads. This is because the bubble structure in the conventional process is unstable, resulting in low material strength.

[0127] Thermal insulation performance: The thermal insulation performance of the conventional process is 0.06 W / m·K, which is far less than that of Example 1 (0.03 W / m·K). This is because the thermal insulation performance is poor due to the uneven cell structure, especially the lack of multi-layer structure expansion treatment during the foaming process, resulting in poor overall thermal insulation performance.

[0128] Although the traditional process is relatively simple, its performance index is far inferior to the technical solution of Example 1. By adopting nano-scale porous materials, nitrogen saturation and multi-layer structure expansion process, Example 1 significantly improves the bubble uniformity, compressive strength and thermal insulation performance of the material.

[0129] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A polyvinylidene fluoride supercritical foaming production process, characterized in that: The following steps are involved: (a) mixing polyvinylidene fluoride with a nano-porous material, wherein the particle size of the nano-porous material is 50-150 nm; (b) using a twin-screw extruder to extrude the mixed polyvinylidene fluoride material into a sheet, and performing a cross-linking treatment after extrusion; (c) preheating the extruded sheet at 220° C. for 10-15 minutes to further enhance the crosslinking reaction; (d) placing the plate into an autoclave, heating it to 250° C., increasing the pressure to 675 bar, and maintaining it for 8 hours, so that nitrogen diffuses into the plate through the nanoporous material; (e) forming uniform bubble nuclei through a rapid depressurization step; (f) The sheet is subjected to a multi-layer expansion treatment in a low-pressure autoclave, and the pressure is gradually reduced to form a multi-layer foam structure.

2. The supercritical foaming production process of polyvinylidene fluoride according to claim 1, characterized in that: The nano-scale porous material is silicon dioxide or aluminum oxide, and the added amount of the nano-scale porous material is 0.5%-5% of the total weight of the polyvinylidene fluoride.

3. The supercritical foaming production process of polyvinylidene fluoride according to claim 1, characterized in that: The screw speed of the twin-screw extruder is set to 50-150rpm, the extrusion temperature is 180°C to 230°C, and the extrusion pressure is controlled between 5-10MPa.

4. The supercritical foaming production process of polyvinylidene fluoride according to claim 1, characterized in that: The thickness of the plate after the preheating step is 5-10 mm.

5. The polyvinylidene fluoride supercritical foaming production process according to claim 1, characterized in that: The pressure reduction rate of the rapid pressure reduction step is 1-5 bar / sec.

6. The supercritical foaming production process of polyvinylidene fluoride according to claim 1, characterized in that: The multi-layer expansion step comprises the following steps: The first expansion is carried out at a pressure of 17 bar to form a high-density core layer, and the expansion multiple is 3 times the original volume; The pressure is reduced to 10 bar and a second expansion is performed to form a medium-density middle layer with an expansion multiple of 5-6 times; The pressure is further reduced to 1-2 bar to form a low-density outer layer with an expansion multiple of 8-10 times.

7. The supercritical foaming production process of polyvinylidene fluoride according to claim 6, characterized in that: The cell density of the high-density core layer is 10^6 to 10^7 per cubic centimeter.

8. The supercritical foaming production process of polyvinylidene fluoride according to claim 6, characterized in that: The cell density of the medium-density middle layer is 10^5 to 10^6 per cubic centimeter.

9. The supercritical foaming production process of polyvinylidene fluoride according to claim 6, characterized in that: The cell density of the low-density outer layer is 10^4 to 10^5 per cubic centimeter.

10. The polyvinylidene fluoride supercritical foaming production process according to claim 1, characterized in that: The foam material is cooled to 60° C. after expansion is completed, with a cooling rate of 5° C. / min.

Citation Information

Cited By

  • Method for efficiently preparing high-magnification PVDF microcellular foamed sheet

    CN122011488A